TESTANDO A TEORIA DA PARIDADE DE PODER DE COMPRA (PPC) NO PERÍODO DE 1995 A 2010 - Santos, Marcelo dos (2011)
The objective of this work is to test the theory of Purchasing Power Parity in its absolute and relative version for Brazil from 1995 to 2010, using econometrics to establish procedures through hypothesis testing to validate or reject the theory of parity Purchasing Power. For analysis the tests Dickey-Fuller (DF), Dickey-Fuller Expanded (ADF) and cointegration tests of Engle and Granger and Johansen Method s will be used. The countries chosen for this study are the U.S. and Brazil, in view of the flow of trade between these countries and their importance in the global economy. Also the price indices IPA and PPI analysis will be considered to validate the theory of Purchasing Power Parity in the version relative and absolute, coming to completion of acceptance on his relative version and rejection on his absolute version.